Silene ohwii (Caryophyllaceae), a replaced name for Melandrium nubigenum - Hsu, Tian-Chuan; Liao, Chun-Kuei; Chung, Shih-Wen; Huang, Wei-Jie (Phytotaxa, 2020)
Silene Linnaeus (1753: 416) (Caryophyllaceae Juss.) is one of the largest genera of flowering plants in the world, consisting of about 700 species (Melzheimer 1988, Morton 2005) the majority of which are distributed in the Mediterranean area (Greuter 1995). The genus is critical from both taxonomic and nomenclatural points of views (see e.g., Petri et al. 2011, Rautenberg et al. 2011, Naciri et al. 2017, Đurović et al. 2018, Iamonico 2018).